ANALISIS SISTEM PENGENDALIAN INTERNAL PROSEDUR PENGGAJIAN PADA SMP GEMBALA BAIK PONTIANAK - B1031131011, STEFFANI CLAUDIA OSA TARIGAS (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
ABSTRACT The purpose of this research are to know how the application of the internal control system of payroll system at Gembala Baik Junior High School Pontianak whether it is effective or not and also to know what are the factors that influence the effectiveness of the implication of the payroll procedure internal control system at Gembala Baik Junior High School Pontianak. This analysis use a descriptive qualitative method, and also used four analysis tools such as organizational structure, flowchart of payroll procedures, internal control questionnaires (ICQ), and compliance test on payroll procedures of Gembala Baik Junior High School Pontianak. Based on research that has been done, it can be concluded that the implementation of the internal control system of payroll procedures have been effective. It is influenced by several factors are an employee who has to understand the systems and procedures adopted, bind up with a good coordination between divisions, and there is a good relationship between the school and the foundation. Keywords: Systems, Procedure, Payroll, Internal Control.